2014
DOI: 10.1249/mss.0000000000000362
|View full text |Cite
|
Sign up to set email alerts
|

Linear/Nonlinear Relations of Activity and Fitness with Children’s Academic Achievement

Abstract: A growing research base suggests the benefits of physical activity (PA) and aerobic fitness for children extend beyond overall health/well-being to include academic achievement (AA). The majority of research studies on relations of PA and fitness with AA have utilized linear-only analytic approaches, thereby precluding the possibility that PA and fitness could have a differing impact on AA for those more/less active or fit. Objective Evaluate both linear and non-linear associations of PA and aerobic fitness w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
70
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 31 publications
(39 reference statements)
12
70
1
1
Order By: Relevance
“…None Aerobic fitness: VERY LOW i 1 study reported no effect of PA intervention on aerobic fitness (Rowland et al 1996); 1 study reported a favourable effect of PA intervention for INT compared with CTRL (Dimitriou et al 2011); and 1 study reported no differential effect of PA intervention on aerobic fitness between INT and CTRL, however, the intervention group decreased from baseline to post-test (Shore et al 2014) Muscular strength and endurance: 1 study reported a favourable effect of PA intervention on upper-body strength for INT compared with CTRL (Dimitriou et al 2011); and 1 study reported no differential effect of PA intervention on muscular fitness; however, the control group improved upper body strength from baseline to post-test (Shore et al 2014) Flexibility: 1 study reported a favourable differential effect of PA intervention for INT compared with CTRL (Dimitriou et al 2011) 1 study reported no differential effect of a PA intervention on flexibility, and an increase from baseline to post-test for the intervention group (Shore et al 2014 Butte et al 2007b;Hands et al 2009;Schofield et al 2009;Ruiz et al 2011;Machado-Rodrigues et al 2012;Martinez-Gomez et al 2012;Hjorth et al 2013;Lambourne et al 2013;Hansen et al 2014;Larouche et al 2014;Saavedra et al 2014) or mixed (favourable and null; 4/18 studies; Rizzo et al 2007;Dencker et al 2010;Kristensen et al 2010;Jimenez-Pavon et al 2013c) o VPA: associations were favourable (11/12 studies; Gutin et al 2005a;Ruiz et al 2006;Butte et al 2007b;Rizzo et al 2007;Lohman et al 2008;Martinez-Gomez et al 2010aKristensen et al 2010;Ottevaere et al 2011;Hay et al 2012;…”
Section: No Serious Imprecisionmentioning
confidence: 99%
See 4 more Smart Citations
“…None Aerobic fitness: VERY LOW i 1 study reported no effect of PA intervention on aerobic fitness (Rowland et al 1996); 1 study reported a favourable effect of PA intervention for INT compared with CTRL (Dimitriou et al 2011); and 1 study reported no differential effect of PA intervention on aerobic fitness between INT and CTRL, however, the intervention group decreased from baseline to post-test (Shore et al 2014) Muscular strength and endurance: 1 study reported a favourable effect of PA intervention on upper-body strength for INT compared with CTRL (Dimitriou et al 2011); and 1 study reported no differential effect of PA intervention on muscular fitness; however, the control group improved upper body strength from baseline to post-test (Shore et al 2014) Flexibility: 1 study reported a favourable differential effect of PA intervention for INT compared with CTRL (Dimitriou et al 2011) 1 study reported no differential effect of a PA intervention on flexibility, and an increase from baseline to post-test for the intervention group (Shore et al 2014 Butte et al 2007b;Hands et al 2009;Schofield et al 2009;Ruiz et al 2011;Machado-Rodrigues et al 2012;Martinez-Gomez et al 2012;Hjorth et al 2013;Lambourne et al 2013;Hansen et al 2014;Larouche et al 2014;Saavedra et al 2014) or mixed (favourable and null; 4/18 studies; Rizzo et al 2007;Dencker et al 2010;Kristensen et al 2010;Jimenez-Pavon et al 2013c) o VPA: associations were favourable (11/12 studies; Gutin et al 2005a;Ruiz et al 2006;Butte et al 2007b;Rizzo et al 2007;Lohman et al 2008;Martinez-Gomez et al 2010aKristensen et al 2010;Ottevaere et al 2011;Hay et al 2012;…”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…Poitras et al n Includes 28 cross-sectional studies (Eiberg et al 2005;Gutin et al 2005a;Andersen et al 2006;Ruiz et al 2006Ruiz et al , 2011Butte et al 2007b;Rizzo et al 2007;Lohman et al 2008;Ortega et al 2008;Hands et al 2009;Schofield et al 2009;Dencker et al 2010;Kristensen et al 2010;Martinez-Gomez et al 2010a;Moliner-Urdiales et al 2010;Ottevaere et al 2011;Hay et al 2012;Machado-Rodrigues et al 2012;Hjorth et al 2013;Jimenez-Pavon et al 2013c;Lambourne et al 2013;Silva et al 2013;Larouche et al 2014;Hansen et al 2014;Santos et al 2014;Saavedra et al 2014;Aggio et al 2015) from 17 unique samples. Five studies reported data from the EYHS (Andersen et al 2006, Ruiz et al 2006Ortega et al 2008;Rizzo et al 2008;Kristensen et al 2010); 6 studies reported data from HELENA (Martinez-Gomez et al 2010a;Moliner-Urdiales et al 2010;Ottevaere et al 2011;Ruiz et al 2011;Martinez-Gomez et al 2012;Jimenez-Pavon et al 2013c); 2 studies reported data from the CoSCIS study (Eiberg et al 2005;Dencker et al 2010).…”
Section: No Serious Imprecisionmentioning
confidence: 99%
See 3 more Smart Citations